Screening for Heart Failure in Patients with Hypertension And/Or Diabetes Using Hand-Held Echocardiography: A Pilot Study - Zi-Xuan Yang; Yu Kang; Xue-Ke Zhong; Qiao-Wei Chen; Yi She; Yun Guo; Xiao-Jing Chen; Hua Wang; Qing Zhang (Global Heart)
Objective: This study aimed to assess the feasibility and cost-effectiveness of hand-held echocardiography-based screening for Stage B or C heart failure among individuals with hypertension and/or diabetes at the High-tech Area Fangcao Community Health Service Center and the Tianfu New Area Huayang Community Health Service Center in Chengdu, China, with the objective of promoting early diagnosis and intensified care. Methods: Patients with hypertension and/or diabetes registered and cared for at two community health service centers (CHSCs; Chengdu, China) with no history of clinical heart failure were recruited between October 2021 and December 2021. By combining symptom assessment (dyspnea and/or edema) and N-terminal-probrain natriuretic peptide (NT-proBNP ≥ 125 pg/ml as the cut-off) levels with HHE for any indexed abnormality in the dedicated semi-quantitative protocol, patients were categorized into heart failure (HF) Stages A, B, and C. The diagnostic accuracy and cost-effectiveness of several pre-specified screening strategies were compared. Results: Of the 423 patients (70 ± 9 years; males, 46.6%) enrolled, 166 (39.2%) were symptomatic and 106 (25.1%) exhibited elevated NT-proBNP levels. Hand-held echocardiography (HHE) abnormalities were detected in 286 (67.0%) patients, with interventricular septum thickening (47.0%) being the most common finding, followed by left atrial enlargement (30.0%). Left ventricular systolic dysfunction was identified in 18 (4.3%) patients. A total of 240 (56.7%) patients were reclassified as HF Stage B and 59 (13.9%) as Stage C. The stepwise strategy of using symptoms for initial stratification, followed by the selection of HHE or NT-proBNP in different circumstances, resulted in 100% accuracy and a 31.3% reduction in costs. Conclusions: HHE-based focused HF screening allows for the early identification of numerous cases of Stage B and mild Stage C HF in high-risk populations. A stepwise screening strategy incorporating symptoms, NT-proBNP, and HHE is feasible and cost-effective and should be adopted in community-based primary care settings.